Teachers’ perceptions, experiences, and challenges in professional development programs in Afghanistan - Qodsya Mastour; Farida Faqiri (Science and Education, 2024)
This study explored school teachers’ perceptions of their professional development programs and the programs’ impact on teachers’ attitudes, knowledge, and practices in Afghanistan. Semi-structured interviews and survey questionnaires are conducted to collect data from ten different schools in Herat Province, Afghanistan. The Qualitative data were thematically analyzed and the quantitative data were analyzed via SPSS software. The result of the study shows that teachers had a positive attitude toward the professional development programs.